Beatriz Sarlo. Clases de literatura argentina. Buenos Aires, Siglo XXI, 2022, 287 - Menestrina, Enzo Matías (Badebec, 2023)
Reseña de Beatriz Sarlo. Clases de literatura argentina. Buenos Aires, Siglo XXI, 2022, 287.